STATUTORY INCOME STREAM AND PERFORMANCE OF LISTED COMMERCIAL BANKS IN NIGERIA (Journal of Contemporary Issues in Accounting, 2026)
The study assessed the effect of statutory income stream on performance of commercial banks listed on the Nigerian Exchange Group. Specifically, the study evaluated the effect of interest income on Return on Assets (ROA) and further ascertained how non-interest income affects the Return on Assets of commercial banks in Nigeria. Relying on the ex-post facto research design, a total of 7 licensed commercial banks with international operational scope was sampled over a period of 12 years ranging from 2013-2024. Descriptive and correlational analyses were preliminarily conducted to summarise the data obtained and analyse the research questions. Hypotheses formulated were tested using panel estimated generalised least square regression analysis. The findings revealed that interest income has a significant effect on the Return on Asset of listed commercial banks in Nigeria such that, Investment securities income had a negative but significant effect on ROA (β = -0.0143; p = 0.0000); loan and advances to banks maintained a positive and statistically significant effect on ROA (β = 0.0009; p = 0.0001); while loan and advances to customers showed a positive and statistically significant effect on ROA (β = 0.0084; p = 0.0000) of listed commercial banks in Nigeria. It was further discovered that that non-interest income has a significant effect on ROA such that credit related fees had a negative but significant effect on ROA (β = -0.0040; p = 0.0003); letters of credit commission had a negative but significant effect on ROA (β = -0.0022; p = 0.0000); electronic banking income had a positive but statistically insignificant effect on ROA (β = 0.0002; p = 0.8905); while account maintenance income had a positive and significant effect on ROA (β = 0.0010; p = 0.0010) of commercial banks listed in Nigeria. In conclusion, bank profitability is influenced by a complex mix of revenue sources, each interacting uniquely with asset returns. The study therefore recommended that the Management of commercial banks should strategically increase lending activities to customers and interbank loans, while reassessing the portfolio of investment securities to minimize their adverse impact on Return on Assets.
Keywords: Account maintenance income; Electronic banking income; Interest Income; Loan & advances Income; Non-Interest Income; Statutory Income Stream